Perspectives of autophagy-tethering compounds (ATTECs) in drug discovery - Yu Ding; Dong Xing; Yiyan Fei; Shouqing Luo; Boxun Lu (Medicine Plus)
Degrader technologies provide unprecedented strategies to tackle diseases caused by pathogenic proteins that are difficult to target by the traditional inhibitor approach. One pioneering technology, proteolysis-targeting chimera (PROTAC), has revolutionized small-molecule drug discovery. However, PROTACs hijack the ubiquitination-proteasome pathway, which is incapable of degrading certain categories of targets. To address this limitation, scientists introduced autophagy-tethering compounds (ATTECs), capitalizing on the autophagosome protein LC3 to selectively break down both pathogenic proteins and organelles. This review explores multiple dimensions of ATTECs, focusing on their mechanisms of action and potential applications in drug discovery.